PENGARUH REMUNERASI TERHADAP KINERJA PEGAWAI KANTOR PENGAWASAN DAN PELAYANAN BEA DAN CUKAI TIPE MADYA PABEAN B PEKANBARU - Lindagusma Lindagusma; Lilis Suriani (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2018)
Employees provide good performance for agency progress, while agencies provide motivation, equal opportunity every employee to grow, and provide appropriate remuneration for performance that has been given employees to the agency. Remuneration itself is a reward or remuneration provided by the agency to the workforce as a result of the achievements it has given in order to achieve the purpose of the agency. This sense implies that its existence within an agency organization can not be ignored. Because, will be directly related to the achievement of agency goals. The purpose of this study is to determine the effect of remuneration on employee performance Supervisory and Service Office Customs and Excise Type of Customs B Pekanbaru. The method used is descriptive and quantitative; Samples are Head of Office, Expenditure Treasurer, Head of Internal Compliance Unit and employees of Customs and Excise Supervisory and Service Office of Type B, B Pekanbaru as much as 94 people. Techniques of collecting interview data and data analysis descriptively through quantitative approach. This study concludes that the remuneration of employees with indicator of remuneration given is reasonable or fair, remuneration given fair or balanced and remuneration given enough to Customs Supervisory and Service Office of Type B of Customs B Pekanbaru in good category. Performance of employees with quality, quantity and time indicators in Customs and Excise Supervisory and Service Office of Type B of Customs B Pekanbaru in good category. Based on the results of statistical tests above it can be concluded that remuneration variables significantly affect the performance of employees in the Office of Supervision and Service Customs and Excise Type Customs B Pekanbaru.